Palazzo Lanza dei Principi di Deliella. From Ernesto Basile’s Archive Drawings to Virtual Reconstruction (diségno, 2022)
The paper investigates Ernesto Basile’s unbuilt project for Palazzo Lanza dei Principi di Deliella in Palermo, through the study of the original drawings (1895-1897). These consist of 15 graphic documents containing 5 plans, 6 elevations and 4 perspective views, representing four versions of the project with different solutions, each of which can be found in fragmentary and incomplete documentation, attributable to different ideational periods.The paper traces, through the redrawing, the path taken by Basile from the first to the last version and graphically tells the evolution of the building’s plan: from the symmetrical courtyard layout of Palladian matrix of the first version, to the “L” configuration of what is presumed to be the final version, the threshold of the modernist turning point.Monge’s projection redrawing of the plans and elevations held in the Fondo Basile of the Department of Architecture at the University of Palermo and the three-dimensional digital reconstructions, accompanied by graphic readings, describe Basile’s architecture, revealing his design process. The analysis carried out was useful for understanding the evolution of the distributive characteristics of the plans and the compositional balance of the elevations. The 3D models allow to visualise the spatial peculiarities of the design solutions analysed and return the image of a hypothetical fragment of the city that was never realised.
Keywords: virtual reconstruction; archive drawings; digital model; Ernesto Basile